2020
DOI: 10.18632/aging.103534
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial derived peptide humanin is a regulator of lifespan and healthspan

Abstract: INTRODUCTION Mitochondria are central to several theories of aging as they are the major producer of both energy and free radicals, they regulate cell apoptosis, and their dysfunction is central to the observed physiological declines that occur during the aging process [1-5]. Similarly, mitochondrial dysfunction is found in many www.aging-us.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 81 publications
2
63
1
1
Order By: Relevance
“…The progression of pathology is also conditioned by insidious aspect of mitochondrial signaling under oxidative stress, such as the persistent activation of UPR mt , which may exacerbate the disruption of neurons in vivo or induce the release of neuroprotective mitokines in AD, such as humanin [ 202 , 203 ]. Humanin reduce the neuroinflammation and the oxidative stress-induced injury in AD, diminishing the level of protein aggregation and of plaque deposition [ 204 , 205 ].…”
Section: Mitochondrial Oxidative Stress and Mito-inflammation In Imentioning
confidence: 99%
“…The progression of pathology is also conditioned by insidious aspect of mitochondrial signaling under oxidative stress, such as the persistent activation of UPR mt , which may exacerbate the disruption of neurons in vivo or induce the release of neuroprotective mitokines in AD, such as humanin [ 202 , 203 ]. Humanin reduce the neuroinflammation and the oxidative stress-induced injury in AD, diminishing the level of protein aggregation and of plaque deposition [ 204 , 205 ].…”
Section: Mitochondrial Oxidative Stress and Mito-inflammation In Imentioning
confidence: 99%
“…Mitochondrial-derived peptides (MDPs) are biologically active peptides derived from small open reading frames (ORF) in the mitochondrial genome [ 12 16 ]. Emerging studies suggest that mtDNA polymorphisms could impact mitochondrial-derived peptides levels.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently with the idea that HN has not only cytoprotective but also anti-inflammatory roles, it has been found that HN has protective roles not only in AD [ 94 ] but also in T2D, CVD and atherosclerosis [ 95 , 99 – 101 ], which are all considered inflammaging-related diseases [ 102 , 103 ]. Moreover, very recently it has been reported that HN, and probably other mitochondria-derived peptides, improves not only health status but also lifespan [ 104 ]. In particular, Yen and co-workers found that the overexpression of HN increases lifespan in C. elegans , while middle-aged mice treated with the potent humanin analogue HNG showed an improvement in health parameters [ 104 ].…”
Section: Mitokines In Immune Responsesmentioning
confidence: 99%
“…Moreover, very recently it has been reported that HN, and probably other mitochondria-derived peptides, improves not only health status but also lifespan [ 104 ]. In particular, Yen and co-workers found that the overexpression of HN increases lifespan in C. elegans , while middle-aged mice treated with the potent humanin analogue HNG showed an improvement in health parameters [ 104 ]. Literature data are still controversial as far as the age-related changes in HN circulating levels.…”
Section: Mitokines In Immune Responsesmentioning
confidence: 99%